AB1020 Evaluation of the Disease Course of Italian Children with Juvenile Idiopathic Arthritis Treated with Etanercept: Preliminary Results in 1019 Patients. (9th June 2015) - Davì, S.; Verazza, S.; Consolaro, A.; Insalaco, A.; Gerloni, V.; Cimaz, R.; Zulian, F.; Lepore, L.; Corona, F.; Conti, G.; Barone, P.; Cattalini, M.; et al.
Abstract : Background: The advent of biologic medications has considerably increased the potential for treatment benefit in juvenile idiopathic arthritis (JIA), with clinical remission being now achievable in a substantial proportion of patients. Objectives: To evaluate the outcome of etanercept (ETN) therapy in Italian children with JIA. Methods: This is a multicenter, observational study that includes all children with JIA who were given ETN at Italian pediatric rheumatology centers after January 2000. Patients were classified in 2 groups: patients who were no longer taking ETN at study start (Group 1); patients who were still receiving ETN at study start (Group 2). Patients in Group 1 underwent only retrospective assessments, whereas patients in Group 2 underwent both retrospective and cross-sectional assessments. The primary outcome of the study were reasons for ETN discontinuation in patients in Group 1, and achievement of the states of inactive disease (ID), minimal disease activity (MDA) and parent- and child-acceptable symptom state (PASS, CASS) in patients in Group 2. The above states were assessed through both formal definitions and JADAS cutoffs. The secondary outcome was the evaluation of frequency and characteristics of ETN-related side effects. Results: So far, the data of 1019 patients (629 in Group 1 and 390 in Group 2) have been collected. Among the 629 patients in Group 1, reasons for ETN discontinuation evaluated in 460 patients included disease remission (48.5%), lack of efficacy (26.1%), and side effects (14.8%). The results of assessment of disease state through formal definitions in 371 children of the 390 children in Group 2 who had already undergone the cross-sectional evaluation were the following: ID 39.7%, MDA 63.0%, PASS 82.4%, CASS 75.8%. The percentages of patients who reached the same disease states assessed through JADAS cutoffs were: ID 45.9%, MDA 61.6%, PASS 70.0%, CASS 66.2%. Serious adverse events were seen in 17 patients and included inflammatory bowel disease (8 pts), tuberculosis (1 pt), CMV hepatitis (1 pt), recurrent pneumoniae (1 pt), varicella complicated by bronchopneumonia (1 pt), acute pancreatitis (1pt), bacterial osteomyelitis (1 pt), bladder carcinoma (1pt), thyroid carcinoma (1 pt); 1 patient died of sepsis. Conclusions: A substantial proportion of children currently receiving ETN were in the states of ID or MDA, or were satisfied with treatment outcome. Half of the patients who had been discontinued from ETN before study start had the medication stopped because of disease remission. Serious adverse events were uncommon. Disclosure of Interest: None declared